(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Kochker neck incision has been gold standard for the thyroid surgery, which is given transversely 2 cm above the sternal notch and 8-12cm in length. In late nineties minimal invasive techniques gained popularity, one of them is by giving small [3-5cm] midline incision. . We conducted a prospective study toassess the outcome thyroid surgery with smaller incision and factors influencing the incision length. Method: The study group comprised of 39 patients underwent thyroid surgery with minimal incision, between March 2014 to February 2016 in surgical department of Sir Ganga Ram Hospital Lahore. All patients were operated by same surgical team. Results: Out of 39pts, 9 patients were male and 30 patients were female. In 16 patients total thyroidectomy was performed and hemi thyroidectomy in 23 patients. Mean length of incision for total thyroidectomy was 4.5cm and 3.6cm in total thyroidectomy. Length of the incision mainly influence by the volume of thyroid tissue, other factors which play minor role are neck circumference and gender. Conclusion: In our study ,using an anterior small-incision, minimal complication rates ,good cosmoses obtained and more postoperative comfort place this thyroidectomy technique higher than other. Both physician’s and patient’s satisfaction may be achieved with careful patient selection.